2006
DOI: 10.1074/jbc.m510069200
|View full text |Cite
|
Sign up to set email alerts
|

NMR Structure of the R-module

Abstract: In the bacterium Azotobacter vinelandii, a family of seven secreted and calcium-dependent mannuronan C-5 epimerases (AlgE1-7) has been identified. These epimerases are responsible for the epimerization of ␤-D-mannuronic acid to ␣-L-guluronic acid in alginate polymers. The epimerases consist of two types of structural modules, designated A (one or two copies) and R (one to seven copies). The structure of the catalytically active A-module from the smallest epimerase AlgE4 (consisting of AR) has been solved recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 59 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…All these positively charged residues are positioned on one side of the active site cleft. The AlgE4-R-module also has a positively charged cleft on the surface of its ␤-helix (18). Connecting the C-terminal residue of the catalytic A-module to the N terminus of the R-module by a peptide bond would create one long ␤-helix protein, in which a continuous long substrate binding groove runs over the surface of the full-length AlgE4 epimerase (18), thus rationalizing the contribution of the R-module to substrate binding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these positively charged residues are positioned on one side of the active site cleft. The AlgE4-R-module also has a positively charged cleft on the surface of its ␤-helix (18). Connecting the C-terminal residue of the catalytic A-module to the N terminus of the R-module by a peptide bond would create one long ␤-helix protein, in which a continuous long substrate binding groove runs over the surface of the full-length AlgE4 epimerase (18), thus rationalizing the contribution of the R-module to substrate binding.…”
Section: Discussionmentioning
confidence: 99%
“…Atomic force microscopy studies have revealed that the AlgE4 A-module binds more strongly to the alginate chain than the complete enzyme, indicating that the R-module is involved in the regulation of the enzyme-substrate binding strength (17). Nevertheless, the R-module on its own is also able to bind to the alginate chain (18).…”
mentioning
confidence: 99%
“…Similar calcium-loaded β-roll structures have been found by X-ray crystallography in the C -terminal part of other RTX proteins, such as the metalloproteases from Serratia marescens and Serratia sp. [ 8 , 11 ] and by NMR in the R-module of the Azotobacter vinelandii calcium dependent mannuronan C-5 epimerase [ 12 ]. The structure at atomic resolution of RTX proteins in the absence of calcium has not been solved thus far due to its IDP behavior, as reviewed below.…”
Section: Introductionmentioning
confidence: 99%
“…Previously the R-module from the smallest epimerase, AlgE4 (A–R), was found to fold as an all parallel β-roll protein similar to the repeats in toxin (RTX) proteins, but with a positively charged shallow grove on the front side with the ability to bind the polyanionic alginate (Aachmann et al 2006, 2005). AlgE4 exhibit by a processive mode of action, while AlgE6 (A-R1-R2-R3) preferentially introduces GG-blocks in the alginate (Campa et al 2004, Hartmann et al 2002).…”
Section: Biological Contextmentioning
confidence: 99%